Deformation and gas flow characteristics of coal-like materials under triaxial stress conditions. (January 2017) - Wang, Gang; Li, Wenxin; Wang, Pengfei; Yang, Xinxiang; Zhang, Shutong
Abstract: The dynamic characteristics of gas flow are often not considered in the simulation test for coal and gas outburst, making coal-like materials hard to meet the required similarity. To solve this issue, based on previous studies on the physical and mechanical properties of coal-like materials and the characteristics of gas adsorption and emission, we investigated the deformation and gas flow characteristics of coal-like materials under triaxial stress conditions using a triaxial servo-controlled seepage equipment for thermo-fluid-solid coupling of coal containing methane. Analysis of the experimental data revealed the relationship of their stress to strain as well as the relationship of their permeability to principal stress difference and strain. In addition, a coal-like material with best seepage dynamic flow characteristics was chosen and its corresponding preparation Scheme 1 was used as the preferable scheme for preparation of class V dangerous seam. The results provide a new idea and research method for further refining preparation of materials similar to coal and gas outburst seam. Highlights: A new idea and research method to improve the similarity of coal-like material for coal and gas outburst simulation is proposed. Analysis of the experimental data revealed the relationship of their stress to strain as well the relationship of their permeability to principal stress difference and strain. A coal-like material with best seepage dynamic flow characteristics was chosen and obtained the preferable scheme for preparation of class V dangerous seam.